Print Mass Media Strategies in Central Java and Yogyakarta Provinces to Survive the Disruption Era - Danar Kristiana Dewi; Ace Sriati Rachman; Sri Sediyaningsih; M Priono; Rachmawati Windyaningrum (IKOMIK: Jurnal Ilmu Komunikasi dan Informasi, 2021)
The emergence of the internet, which has the power of convergence and multiplatform, terminates the information boundaries. The information flow streaming through the internet creates numerous changes in various lifelines. One of the changes that are experienced is the information shift from print to online. This condition significantly affects print media companies, where customers and advertisers in newspapers begin migrating to a new platform, the internet. It becomes a big challenge for print media in addition to production costs that increase every year. In this era, if the print media do not immediately take action to adapt and innovate, it will be difficult to survive. Observing this development, it is essential to research to determine the strategies implemented by print media companies that currently exist to survive the disruption era. This study implemented a qualitative research method. This study’s results indicate that the print media's survival strategies are innovation, collaboration, maintaining good relationships with customers, and strengthening the journalistic content production to be more attractive.